Value of Mehran risk score in assessing the risk of contrast-induced acute kidney injury in patients who underwent percutaneous coronary intervention - Doan, Khanh Hung; Hoang, Anh Tien; Nguyen, Vu Phong; Ngo, Viet Lam; Duong, Minh Quy (Tạp chí Y Dược Huế, 2025)
Objectives: In patients who underwent Percutaneous coronary intervention (PCI), contrast-induced acute kidney injury (CI-AKI), which is defined as a blood creatinine increase by > 0.5 mg/dl (44.2 mmol/l) or > 25% of the initial creatinine value within 48 hours after intervention, is one of the severe complications of the procedure. We conducted this study to assess the Mehran risk score in patients who underwent PCI; the prognostic value of the Mehran risk score in the risk of CI-AKI; and to follow up the kidney function after three months and six months. Materials and methods: We analyzed 217 patients who underwent PCI from 01/2020 to 03/2021 at Hue University of Medicine and Pharmacy Hospital. We calculated the Mehran risk score, investigated the characteristics related to CI-AKI, and followed up on kidney function after three and six months. Results: Patients with CI-AKI had an average Mehran risk score of 10.92 ± 6.05, significantly higher than patients without CI-AKI with 3.87 ± 3.71. In the multivariate regression analysis, Hypotension, Age > 75, and Diabetes were independently associated with CI-AKI. The cut-off value for risk of CI-AKI of Mehran risk score was > 10, with a sensitivity of 66.7% and a specificity of 88.3%. The kidney function improved significantly in patients with CI-AKI after three months of follow-up. There were three patients with EFGR < 60 ml/min/1.73 m2, and these results were maintained for six months of follow-up. Conclusions: Mehran risk score had prognostic value in assessing CI-AKI in patients who underwent PCI. Hypotension, age > 75, and diabetes are independent risk factors for CI-AKI.